Mammary Analogue Secretory Carcinoma of the Parotid Gland: A Third World Country Perspective—A Case Series - Huzaifah Salat; Ramiz Mumtaz; Mubasher Ikram; Nasir Ud Din (Case Reports in Otolaryngology)
Mammary analogue secretory carcinoma (MASC) is a recently described pathological entity in major salivary glands, which was first described by Skálová et al. in 2010. Since then only a limited number of case reports/series have been published describing this tumor with the majority of them discussing the genetic and cytoarchitectural aspect of this tumor. Keeping this in view with the lack of clinical correlation with regard to this tumor, we present our approach to management of two such cases which, according to the best of our knowledge, are the first 2 cases presenting in the South Asian continent. Both patients were diagnosed and managed at Aga Khan University Hospital, Karachi, Pakistan.